Photothermally-driven thermo-oxidative degradation of low density polyethylene: heterogeneous heating plus a complex reaction leads to homogeneous chemistry. (9th September 2019) - Firestone, Gabriel; Huang, Honglu; Bochinski, Jason R; Clarke, Laura I
Abstract: Photothermal heating from embedded nanoparticles, a process whereby visible light is converted into heat resulting in a high temperature in each particle's immediate vicinity, was utilized to degrade low density polyethylene (LDPE) via thermo-oxidation. The spatially-varying steady-state photothermal temperature field is a potential mechanism by which ambient light (e.g. sunlight) could be used to drive chemical reactions within solid materials and may result in a non-uniform pattern of products, an advantage or disadvantage depending on application. Novel approaches to control polymer degradation are of interest because of the goal of remediating plastic waste, including autonomous means to minimize its effect when unconfined in the environment. For thermoplastic auto-oxidation, heterogeneous degradation would likely enhance deleterious micro-fragmentation however, the multi-step, multi-site nature of the reaction mitigated the temperature non-uniformity. A photothermally-heated LDPE nanocomposite with silver nanoparticle and cobalt-stearate additives showed degradation, characterized by ultraviolet–visible and Fourier-transform infrared absorption spectroscopy, electron microscopy, and mechanical testing, nearly identical to that resulting from uniform conventional treatment at the same average temperature.